Analisis Yuridis Terkait Penggunaan Cek Kosong dalam Transaksi Jual Beli: (Studi Kasus Pembelian Alat Berat dengan Cek Kosong Oleh Pengusaha di Tanjung Pinang) - Denise Asha Aliqa; Syahbila Amanda Putri Rangkuti; Kevin Pasha Putra Pratama; Mohammad Dzaki Rabbani (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
a case of fraud using a blank check committed by a businessman in Tanjungpinang, Riau Islands. This research aims to analyze the criminal act of fraud committed by the businessman in the sale and purchase of heavy equipment and the legal consequences that can be imposed. The research method used is a qualitative method with a case study approach, through analysis of news published by Kompas.com. The results showed that a businessman named Hendy (33) was suspected of having committed a criminal act of fraud and/or embezzlement in a heavy equipment purchase transaction using a blank check. Hendy is alleged to have deceived the victim by giving a check that did not have sufficient funds in the account. Hendy's actions can be subject to articles related to criminal acts of fraud and / or embezzlement in the Criminal Code (KUHP). In addition, Hendy is also potentially subject to civil sanctions due to his actions that harm other parties. This article concludes that the practice of fraud using blank checks in business transactions, especially the sale and purchase of heavy equipment, is a criminal offense that must be dealt with firmly by law enforcement officials to provide a deterrent effect and ensure legal certainty for business actors.